1994
DOI: 10.1159/000139195
|View full text |Cite
|
Sign up to set email alerts
|

Active [<sup>3</sup>H]-Dopamine Uptake by Human Lymphocytes: Correlates with Serotonin Transporter Activity

Abstract: The main objective of the present investigation was to determine whether the uptake of [3H]-dopamine in human lymphocytes is mediated through a serotonin transporter. This was examined by studying the effects of various monoamine uptake inhibitors on the uptake of [3H]-dopamine in human lymphocytes. Among the compounds tested, indatraline, imipramine and fluoxetine, selective inhibitors of neuronal serotonin transporter, were the most potent inhibitors of [3H]-dopamine uptake i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
14
1
1

Year Published

1995
1995
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(17 citation statements)
references
References 6 publications
1
14
1
1
Order By: Relevance
“…10), indicating that DA entered the cell via the hSERT. Indeed, functional SERT proteins are capable of transporting DA into 5-HT cells (Schmidt and Lovenberg, 1985;Faraj et al, 1994). Although the mechanism by which MDMA/MDA and the metabolites stimulate DA uptake by the hSERT is not known, Saldana and Barker (2004) have recently reported that elevated temperature alters SERT-mediated 5-HT and DA transport, such that the relative selectivity of the SERT for DA increases significantly at the higher temperature.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…10), indicating that DA entered the cell via the hSERT. Indeed, functional SERT proteins are capable of transporting DA into 5-HT cells (Schmidt and Lovenberg, 1985;Faraj et al, 1994). Although the mechanism by which MDMA/MDA and the metabolites stimulate DA uptake by the hSERT is not known, Saldana and Barker (2004) have recently reported that elevated temperature alters SERT-mediated 5-HT and DA transport, such that the relative selectivity of the SERT for DA increases significantly at the higher temperature.…”
Section: Discussionmentioning
confidence: 99%
“…MDMA-induced serotonergic neurotoxicity also seems to be coupled to increases in dopamine (DA) release (Bankson and Cunningham, 2001). MDMA stimulates the release of DA (Gudelsky and Nash, 1996;Koch and Galloway, 1997), and functional SERTs are capable of transporting DA into 5-HT cells (Schmidt and Lovenberg 1985;Faraj et al, 1994). The subsequent monoamine oxidase (MAO)-B-mediated oxidation of DA within the 5-HT nerve terminal may contribute to MDMA-induced generation of reactive oxygen species (ROS; Sprague and Nichols, 1995;Sprague et al, 1998).…”
mentioning
confidence: 99%
“…Some of these adaptive changes could come from involvement of redundant monoaminergic systems in cocaine reward. Since each transporter displays significant affinities for each monoamine (Faraj et al, 1994;Giros et al, 1994;Gu et al, 1994;Eshleman et al, 1999), the absence of its cognate transporter might allow a monoamine to diffuse further from its site of release and be accumulated by another transporter.…”
Section: Introductionmentioning
confidence: 99%
“…It was reported that the inhibitory eŠects of indatraline on uptake of [ 3 H]-DA into human lymphocytes were stronger than those of nomifensine. 8) Although nomifensine is known as an inhibitor of DA-transporter, it also bind to norepinephrine transporter with high a‹nity. 19) Thus, the uptake of Trp-P-1 may be mediated not only by DA and 5-HT transporters but also by the norepinephrine transporter, suggesting that monoamine transporters play as important roles in the uptake of Trp-P-1.…”
Section: Discussionmentioning
confidence: 99%
“…6) In addition, the transport systems of DA and 5-HT exist not only in synapses but also in platelets and lymphocytes. 7,8) Trp-P-1 was detectable in platelets for at least 9 days after oral administration to rabbits. 9) In this study, we investigated how Trp-P-1 is incorporated into splenocytes, thymocytes, and hepatocytes, and stimulates the apoptotic pathway.…”
mentioning
confidence: 97%